Novel gold nanoparticles of drought tolerance enabler GYY4137 - Binase, Ntombikayise (University of the Western Cape, 2019)
>Magister Scientiae - MSc === Different nanoparticles have the ability to improve plant tolerance to drought stress. In the study we report for the first time novel morpholin-4-ium 4-methoxyphenyl (morpholino) phosphinodithioate capped- gold nanoparticles (GYY4137-capped AuNPs). The GYY4137 is a slow releasing hydrogen sulfide (H2S) donor. The GYY4137 AuNPs compared to preliminary experiments of L-serine and L-threonine gold nanoparticles. The nanoparticles were prepared using a simple reflux reduction method in a rolling boil flask at 80 oC. The uncapped GYY4137-AuNPs were relatively stable and had surface plasmon resonance at 562 nm compared to 524 nm and 560 nm of serine-AuNPs and threonine-AuNPs. The nanoparticles were capped with different concentrations (0.1-5 %) of water-soluble poly (ethylene) glycol (PEG) (Mw300) and 0.2% chitosan. The PEG did not fully encapsulate the gold nanoparticles, while the chitosan successfully produced positively charged gold nanoparticles. The formation of chitosan capped GYY4137-AuNPs were verified with UV-Visible spectroscopy (UV-Vis), High Resolution Transmission electron microscopy (HRTEM), Dynamic Light scattering (DLS) and the Zetasizer. The UV-Vis, HRTEM and STEM verified chitosan capped nanoparticles had a surface plasmon resonance peak at 560 nm, with icosahedral, tetrahedron and spherical shaped nanoparticles as the serine-AuNPs that absorb at 560 nm. The agglomerated threonine-AuNPs had a maximum absorbance peak at 524 nm. The chitosan GYY4137-AuNPs had hydrodynamic size of 347.9 nm and zeta potential of + 47 mV, while serine-AuNPs and threonine-AuNPs had hydrodynamic size of 110 nm, zeta potential of -2.9 mV and -230 mV respectively. The polydispersity index (PDI) of the chitosan capped gold nanoparticles was 0.357 compared to 0.406 of both the amino acid gold nanoparticles. The polydispersity index (PDI) showed that the nanoparticles were polydispersed nanoparticles with broad size range as confirmed by the HRTEM and STEM results/ of chitosan capped GYY4137-AuNPs. The sizes of the nanoparticles were 100 nm and 60 nm for GYY4137-AuNPs while the size serine-AuNPs were 60 nm. The gold nanoparticles structural compositions were further confirmed by energy-dispersive X-ray spectrometry (EDX) and Attenuated total reflection infrared spectroscopy (ATR-IR). EDX results proved successful gold nanoparticles synthesis by presence of the element Au in all three nanoparticles and the chitosan GYY4137-AuNPs had 48. 56 wt. % of gold. The FTIR-ATR new bands formation shows that new chemical bonds are formed between the reducing agents, the precursor gold salt solution and capping agents. The shifts showed successful encapsulation with chitosan in GYY4137-AuNPs. The chitosan encapsulation improved surface charge and reactivity of the gold nanoparticles to improve delivery of the hydrogen sulfide donor GYY4137 for later applications to plants.